Conservative aesthetic management of dental fluorosis using microabrasion with two different acidic compounds in pediatric patients: A report of two cases - Nehal Ahmad; Saima Yunus Khan; Divya Sanjay Sharma; Mahendra Kumar Jindal; Imam Azam; Mohammad Atif (Arbu Academic Publishing, 2024)
Dental fluorosis is a subsurface hypomineralization condition, characterized by yellow to dark brown stains, with or without enamel porosity and pitting. Due to aesthetic concerns, children with discolored anterior teeth often experience negative impacts on their psychological, emotional, and social development. Treatment options include porcelain laminates or veneers, direct resin restorations, and crowns. However, these methods are invasive and require significant enamel reduction, making them unsuitable for children due to their enlarged pulp chambers. Microabrasion is the least invasive and safest treatment for children with fluorosis. This technique involves using a combination of 37% phosphoric acid gel with extra fine grain pumice, 18% hydrochloric acid in pumice, or 6.6% and 10% hydrochloric acid with silica carbide particles. The mixture is applied with a slowly rotating rubber cup to the areas of discoloration or white opacities. An additional benefit of microabrasion is that it leaves the enamel surface highly polished, reducing the growth of cariogenic bacteria and increasing resistance to demineralization. This case report describes two instances of dental fluorosis treated with microabrasion using different acidic compounds in two pediatric patients, resulting in clinically acceptable and aesthetically pleasing outcomes.